Potential Effects of Alkaloid vindolicine Substances in Tapak Dara Leafs (Catharanthus roseus (L.) G. Don) in Reducing Blood Glucose Levels - Agung B S Satyarsa (Universitas Kristen Maranatha, 2019)
Diabetes mellitus is a degenerative disease that commonly found and related to an unhealthy lifestyle and genetic factors. Current management of diabetes mellitus includes control of blood sugar levels and prevention of complications. Recent studies found that many phytochemicals have the potential to control blood sugar levels in patients with diabetes. Alkaloid substances from leaves of Tapak Dara have an effect on decreasing blood glucose. This review article aims to describe the potential effects of the Alkaloid vindolicine from Tapak Dara leaves (Catharanthus Roseus L.) in reducing blood glucose levels in patients with type 2 diabetes mellitus. The activity of vindolicine alkaloid against ? cells in previous studies has shown to improve ? cells activity and induce insulin secretion thus preventing further hyperglycemia. In addition, the vindolicine alkaloid also has a role in activating pancreatic ?-TC6 cells and carrying out an immediate reaction in blood vessels. As conclusion, further research is needed to prove the maximum effect of the utilization of tread leaf extract as well as the toxicity test to determine the toxic effects of the alkaloid substances in the tread leaf. Keywords: Type 2 Diabetes Mellitus, Vindolicine Alkaloid, Tapak Dara, blood glucoselevels